Investigation of Suitable Detection Angles for Carbon-Ion Radiotherapy Monitoring in Depth by Means of Secondary-Ion Tracking - Ghesquière-Diérickx, Laura; Schlechter, Annika; Félix-Bautista, Renato; Gehrke, Tim; Echner, Gernot; Kelleter, Laurent; Martišíková, Mária (Frontiers in Oncology, 2021)
The dose conformity of carbon-ion beam radiotherapy, which allows the reduction of the dose deposition in healthy tissue and the escalation of the dose to the tumor, is associated with a high sensitivity to anatomical changes during and between treatment irradiations. Thus, the monitoring of inter-fractional anatomical changes is crucial to ensure the dose conformity, to potentially reduce the size of the safety margins around the tumor and ultimately to reduce the irradiation of healthy tissue. To do so, monitoring methods of carbon-ion radiotherapy in depth using secondary-ion tracking are being investigated. In this work, the detection and localization of a small air cavity of 2 mm thickness were investigated at different detection angles of the mini-tracker relative to the beam axis. The experiments were conducted with a PMMA head phantom at the Heidelberg Ion-Beam Therapy Center (HIT) in Germany. In a clinic-like irradiation of a single field of 3 Gy (RBE), secondary-ion emission profiles were measured by a 2 cm2 mini-tracker composed of two silicon pixel detectors. Two positions of the cavity in the head phantom were studied: in front and in the middle of the tumor volume. The significance of the cavity detection was found to be increased at smaller detection angles, while the accuracy of the cavity localization was improved at larger detection angles. Detection angles of 20° – 30° were found to be a good compromise for accessing both, the detectability and the position of the air cavity along the depth in the head of a patient.